Knowledge, attitude, and practice of vasoactive agents infusions: Development and psychometric properties of a questionnaire with chinese clinical nurses - Yanfang Huang; Yi Chen; Yaping Fang; Junjie Mou; Shiqin Li; Xianying Lei; Yuxin Li; Zhongping Ai (PLoS ONE, 2025)
Background Inconsistencies with guidelines or standards regarding nurses’ practice of vasoactive agent infusion have been documented. Adequate knowledge and positive attitudes are critical for compliance. However, there are currently no validated tools specifically designed to measure the knowledge and attitudes related to vasoactive agent infusions among nurses. Objective The aim of this study was to develop and test the validity and reliability of the Chinese mainland version of Knowledge, Attitude, and Practice of Vasoactive Agents Infusions Questionnaire among nurses. Methods The initial questionnaire items were developed through a comprehensive literature review, expert consultation, and pilot study. From February to June 2024, cross-sectional data were collected using convenience sampling from 538 nurses across 9 hospitals in Sichuan Province, China. The reliability and validity of the scale were evaluated through internal consistency reliability, inter-rater reliability, exploratory factor analysis, and confirmatory factor analysis. Results The final version of the questionnaire included 33 items across 3 dimensions, explaining 78.04% of the variance, with item loadings ranging from 0.56 to 0.89. The content validity index ranged from 0.91 to 1.00, and the scale-level content validity index was 0.98.The overall Cronbach’s α for the questionnaire was 0.96, with Cronbach’s α for each dimension ranging from 0.96 to 0.98. The test-retest reliability for the entire questionnaire was 0.90, and for each dimension, it ranged from 0.90 to 0.94 (p < 0.05). The confirmatory factor analysis demonstrated acceptable fit indices for the three-dimensional model: χ²/(df) = 1.135, p = 0.200, RMSEA = 0.024, CFI = 0.986, TLI = 0.985, GFI = 0.884, and NFI = 0.895. Conclusion The Knowledge, Attitude, and Practice of Vasoactive Agents Infusions Questionnaire demonstrates good reliability and validity, making it a reliable measurement tool for assessing nurses’ attitudes and knowledge related to vasoactive agents’ infusions. This version will facilitate further research and advancements in this specific field of study.